Odd women? : spinsters, lesbians and widows in British women's fiction, 1850s-1930s - Liggins, Emma (Manchester ; New York : Manchester University Press, 2014)
Women outside marriage between 1850 and the Second World War were seen as abnormal, threatening, superfluous and incomplete, whilst also being hailed as 'women of the future'. Before 1850 odd women were marginalised, minor characters, yet by the 1930s spinsters, lesbians and widows had become heroines. This book considers how Victorian and modernist women's writing challenged the heterosexual plot and reconfigured conceptualisations of public and private space in order to valorise female oddity.
Description based on online resource; title from PDF title page (EBSCO, viewed August 16, 2016).
Includes bibliographical references and index.
English.
JSTOR
Keywords: English fiction -- 19th century -- History and criticism; English fiction -- 20th century -- History and criticism; English fiction -- Women authors -- History and criticism; Women in literature; Single women in literature; Widows in literature; Lesbians in literature; Roman anglais -- 19e siècle -- Histoire et critique; Roman anglais -- 20e siècle -- Histoire et critique; Femmes dans la littérature.; Femmes seules dans la littérature.; Veuves dans la littérature.; Lesbiennes dans la littérature.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; HISTORY / Modern / 16th Century; English fiction; English fiction -- Women authors; Lesbians in literature; Single women in literature; Widows in literature; Women in literature; 1800-1999; Criticism, interpretation, etc